Evolving Selves: A Narrative Inquiry Into The Role of Reflective Journaling in Shaping Experienced EFL Teachers’ Professional Identity - Maulana, Arli; Supriatna, Deri; Sulaeman, Dedi; Ruminda; Imani, Anugrah (PROJECT (Professional Journal of English Education), 2025)
This study explores the evolving nature of professional identity among experienced English as a Foreign Language (EFL) teachers, with a specific focus on the role of reflective journaling. While much of the existing literature has emphasized the identity development of pre-service or novice teachers, this research highlights how identity continues to transform throughout a teacher’s career. Using a qualitative narrative inquiry approach, the study involved six experienced EFL teachers who responded to open-ended reflective questions. Data were analyzed thematically, drawing from both participant narratives and NVivo-style coding, to identify patterns in reflective practice and professional self-understanding. The findings reveal that reflective journaling, whether formal, informal, or mental, serves as a powerful mediational tool for self-awareness, pedagogical growth, and emotional resilience. Participants reported that reflection helped them navigate institutional pressures, revise teaching philosophies, and reaffirm their commitment to student-centered learning. Themes such as motivation, personal values, emotional tension, and adaptability emerged as central to their reflective narratives. Additionally, teachers offered peer-oriented advice, further reinforcing reflection as a shared and generative practice within the EFL community. This study contributes to the discourse on lifelong teacher development by emphasizing the transformative and sustaining role of reflective practice in shaping teacher identity beyond the early stages of teaching.